The Effect Of Competence, Work Experience, Work Environment, And Work Discipline On Employee Performance - I Nyoman Tri Sutaguna; Muhammad Yusuf; Rian Ardianto; Pawit Wartono (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to determine the effect of competence, work experience, work environment, discipline on employee performance. The sampling method uses the census method with a total sample of 46 people. Data collection using the method of observation, interviews and questionnaires. The collected data will be processed in several stages. The first is descriptive analysis. Both multiple linear analyzes. The three data quality tests consist of a validity test and a reliability test. The four classical assumption tests consist of the normality test, heteroscedasticity test, autocorrelation test and multicollinearity test. The five hypothesis tests consist of a T test (partial test), F test (simultaneous test) and a test of the coefficient of determination. The results show that partially the competence variable has no significant effect on employee performance. Work experience variable has no significant effect on employee performance. Work environment variables have a significant effect on employee performance. The work discipline variable has no significant effect on employee performance. Simultaneously all the variables used in this study have a significant effect on performance